Optimalisasi Belanja Daerah Kota Surabaya Sebagai Instrumen Pembangunan Daerah Bidang Pendidikan : Studi Tahun Anggaran 2025 - Arnelita Ayu Az-zahwa; Herdiani Romadhona; Annisa Aulia Rahmah; Blezend Syahrira Rona Maynando; Yesha Verlita Evelin; Icha Chelsea Elisabeth Naibaho; Revienda Anita Fitrie; Melda Fadiyah Hidayat (Jurnal Media Administrasi, 2026)
This study aims to analyze the optimization of regional expenditure in the education sector of Surabaya City for the 2025 fiscal year in supporting regional development. The research uses a descriptive qualitative approach through observation, interviews, and documentation studies conducted at the Surabaya City Education Office. Data were obtained from relevant stakeholders involved in education budget management and supported by official documents related to policies and the implementation of education programs. The results show that the management of education expenditure has been aligned with the Regional Medium-Term Development Plan (RPJMD) and applies the money follow program principle, which prioritizes programs based on community needs and development priorities. Programs such as Regional School Operational Assistance (BOPDA), educational assistance for students, school infrastructure development, and community-based learning innovations have contributed to expanding access to education, improving the equity of educational services, and reducing dropout rates. In addition, the use of monitoring systems, periodic evaluation, and the involvement of multiple stakeholders in supervision has strengthened transparency and accountability in budget management. However, several challenges remain, including limited implementation time, procurement constraints, and economic conditions such as inflation. Overall, education expenditure in Surabaya has been managed relatively well in terms of effectiveness, efficiency, and accountability while still requiring continuous improvement